Analisa Pengaruh Kepadatan, Kesesakkan dan Sosial Ekonomi Terhadap Kesejahteraan Psikologis (Psychological Well-Being) Ibu Rumah Tangga - Febriyanti, Eka; Saam, Zulfan; Wahyuni, Sri (Jurnal Kesehatan Komunitas, 2024)
The level of psychological well-being is a form of mental health through the achievement of the individual's relationship with the surrounding environment, consisting of social interactions, personal relationships, and life satisfaction. The purpose of this study was to analyze the effect of density, tightness, and socioeconomic status on the psychological well-being of housewives (IRT). The research method is correlated with a cross-sectional design and sampling technique using simple random sampling totaling 171 IRT. The place of research is in one of the coastal areas of Pekanbaru City, Riau. The questionnaire used is divided into 4, namely density, tightness, socio-economic, and Ryff's Psychological Well-Being Scale (RPWB). The results of the study found that there were problems of density (62.6%), social congestion (5.3%), and space congestion (6.4%) as well as low economic problems (58.5%). The results of this study indicate that there is no relationship between density (p = 0.158) of crowding (p = 0.693) and socioeconomic (p = 0.777), with the level of psychological well-being (p > 0.05). The researcher suggests that further studies are needed on the factors that influence people living in densely populated areas based on the values ​​and culture they hold.